2019
DOI: 10.1186/s13287-019-1294-x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional dopaminergic neurons from human spermatogonial stem cells to rescue parkinsonian phenotypes

Abstract: Background Recent progress in the induced generation of dopaminergic (DA) neurons from different types of stem cells or reprogrammed somatic cells holds tremendous potential for the treatment of Parkinson’s disease (PD). However, the lack of a reliable source for cell replacement therapy remains a major limitation in the treatment of human neurological disorders. Additionally, the current protocols for in vitro differentiation or cell reprogramming to generate human DA neurons are laborious, time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…This rapid differentiation is caused by the block of the two signaling pathways that utilize SMADs for transduction: BMP and TGF-β. Starting from this dual SMAD inhibition, it is possible to generate DA neurons from hESCs, hiPSCs, and adult stem cells and, as recently evidenced, also from perinatal stem cells [20,[34][35][36][37][38][39][40].…”
Section: Chemical Compounds For Generation Of Da Neurons From Stem Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…This rapid differentiation is caused by the block of the two signaling pathways that utilize SMADs for transduction: BMP and TGF-β. Starting from this dual SMAD inhibition, it is possible to generate DA neurons from hESCs, hiPSCs, and adult stem cells and, as recently evidenced, also from perinatal stem cells [20,[34][35][36][37][38][39][40].…”
Section: Chemical Compounds For Generation Of Da Neurons From Stem Cellsmentioning
confidence: 91%
“…Recently, it has been shown that also human mesenchymal stromal cells (hFM-MSCs) isolated from the amniochorionic membrane [44] can acquire a DA phenotype when treated with the small molecules cocktail used by Kriks et al [20]. In the field of adult stem cells, valproic acid was shown to cooperate in DA differentiation of human spermatogonial stem cells when added to a conditioned medium from olfactory ectomesenchymal cells together with the small molecules SHH, RA, SB431542, FGF8, TGF-β3, and GDNF: the derived DA neurons cells were able to engraft and survive in a PD mouse model, partially rescuing the PD phenotype [34].…”
Section: Chemical Compounds For Generation Of Da Neurons From Stem Cellsmentioning
confidence: 99%
“…Chiu et al, on the other hand, state that finger motion analysis was used to test the goniometry of finger joints [11]. Based on the survey, the dopaminergic image in the brain is considered as an authentic method for the identification of PD [12]. In gait dynamics, continuous effects of PD were noticed.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant cells, known as induced pluripotent stem (iPS) cells, were developed via retroviral delivery of various transcription factors (e.g., Oct3/4, Sox2, c-Myc, and Klf4) to adult dermal fibroblasts [ 18 , 19 , 20 ], hepatocytes, gastric epithelial cells, and even neural stem cells [ 21 , 22 ]. However, the practicality of utilizing different stem cells in clinical settings remains limited due to the ethical and safety concerns over their source [ 23 ]. In addition, current protocols for inducing differentiation into specific cell lineages are inefficient, time-consuming, technically complex, and are not cost effective given the requirement for multiple induction materials [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, we demonstrated that porcine gonocytes are capable of spontaneous dedifferentiation into more primitive stages that express ES cell markers such as SSEA-1, POU5F1, NANOG, and E-cadherin [ 17 ]. This is especially important since in vitro dedifferentiation and trans-differentiation of germ cells in previous reports required coculturing with somatic cells from other species and/or supplementation of the media with multiple exogenous factors [ 7 , 13 , 23 ]. In the present study, we used our recently developed culture conditions to obtain a population of ES-like cells that express pluripotency markers from porcine gonocytes, and then further evaluated their teratoma formation potential using an in vivo implantation assay.…”
Section: Introductionmentioning
confidence: 99%